Impacts of Sand Burial and Wind Erosion on Regeneration and Growth of a Desert Clonal Shrub - Fan, Baoli; Zhao, Changming; Zhang, Xiaowei; Sun, Kun (Frontiers in Plant Science, 2018)
Sand burial and wind erosion caused by sand movement are common phenomena in desert environments, but the effects on clonal shrub have rarely been investigated. Here, we assessed how sand movements affect the population regeneration capacity of juvenile clonal fragments of the shrub Calligonum mongolicum growing in mobile desert sand dunes. We investigated the population status and natural regeneration capacity in three types of mobile dunes (heavy wind erosion, heavy sand burial and moderate sand burial). Clonal propagation of C. mongolicum was markedly different across sites. Moderate sand burial sites had the largest ramet density and bud number per unit length of rhizome, and the overwinter survival rate was significantly higher at sand burial sites than at wind erosion sites, suggesting that C. mongolicum may have well adapted to the moderate sand burial environment. We further examined the effects of clonal integration on clonal regeneration of this species. Physiological, biochemical and morphological characteristics of parent and daughter ramets growing in heterogeneous sandy habitat (sand burial or wind erosion) were measured. The results showed that being connected or severed from the maternal plant critically determined survival of daughter ramets on wind eroded rhizomes. When eroded rhizomes remained connected, the mother ramets had the highest chlorophyll a, b and a + b contents. However, both the mother plant and the daughter ramets undergoing erosion had higher proline and soluble protein levels than sand buried ramets. Meanwhile, the daughter ramets undergoing sand burial had higher photosynthetic rates (Pn), chlorophyll fluorescence parameters (Fm and Fo), and phenotypic traits of assimilating shoots i.e. node number, length and volume than wind-eroded ramets. However, significant differences with mother plants, whether connected or severed, were very limited. It was concluded that moderate sand burial environments promoted clonal reproduction and growth of C. mongolicum. Additionally, physiological integration with mother raments in favorable conditions can alleviate stress on daughter ramets exposed to wind erosion. This physiological effect may do not occur for sand buried daughter ramets. These survival strategies and phenotypic responses should be carefully considered in shrub and sand dune management in sand fixation plantations of C. mongolicum.